Global characterization of GH3 family glycoside hydrolase genes in Fusarium verticillioides and functional analysis of FvGH3-6 - Xiaojie Zhang; Xiaojie Zhang; Pengliang Duan; Pengliang Duan; Shaoqi Shi; Shaoqi Shi; Manli Sun; Manli Sun; Ning Liu; Ning Liu; Zhiyan Cao; Zhiyan Cao; et al. (Frontiers in Microbiology)
To clarify the roles of glycoside hydrolase 3 (GH3) family genes in the growth, development, and pathogenicity of Fusarium verticillioides, GH3 family genes were identified in the genome by bioinformatics software, and their expression levels in the infection process of F. verticillioides were analyzed using transcriptome data. The FvGH3-6 gene was knocked out and complemented via genetic transformation to explore the role of F. verticillioides. The results demonstrated that a total of 19 GH3 family genes were identified in the genome of F. verticillioides, which were located on 11 chromosomes, encoding amino acids ranging from 559 to 1,034, with relative molecular weights between 61.20 and 113.97 kDa, and containing 1–6 exons. Transcriptome data indicated that during the infection of maize kernels by F. verticillioides, the expression of nine genes, including FvGH3-6, was upregulated at different stages. Knockout of the FvGH3-6 gene did not impact the mycelial growth rate of F. verticillioides but reduced the sporulation ability. Compared with the wild type, the pathogenicity of FvGH3-6 knockout mutants towards maize grains and stems was weakened. The above results suggest that the glycoside hydrolase gene family participates in the pathogenicity of F. verticillioides, and the FvGH3-6 gene plays a significant role in the conidia production and pathogenicity of F. verticillioides.